The Effect of Star Jump Games on Children’s Gross Motor Skills: An Educational Management Perspective - Louisa Elvinarosa Erieka Putri; Yes Matheos Lasarus Malaikosa; Mallevi Agustin Ningrum; Dhian Gowinda Luh Safitri (Journal of Educational Management Research, 2026)
This study aims to examine the effect of Star Jump games on children’s gross motor skills from an educational management perspective, particularly in managing physical activity learning in early childhood education. A quantitative approach with a quasi-experimental nonequivalent control group design was employed, involving 28 children divided into experimental and control groups. Data were collected through structured observation using a gross motor skill assessment instrument focusing on body balance and movement accuracy, and analyzed using the Wilcoxon Signed Rank Test and the Mann–Whitney U Test. The results revealed a significant improvement in gross motor skills among children in the experimental group after the implementation of Star Jump games compared to the control group. These findings indicate that well-planned and systematically managed movement-based learning activities effectively enhance children’s balance and movement precision. From an educational management perspective, the study underscores the importance of organizing, implementing, and evaluating engaging physical activity programs to support gross motor development. Therefore, Star Jump games can be considered an effective and enjoyable alternative for managing physical activity learning in early childhood education.